Pengaruh Store Atmosphere dan Kualitas Layanan Terhadap Kepuasan Konsumen (Studi Kasus di Rumah Makan Asela Sampang) - Iin Sofiyatin Hamidiyah; Lilis Sugi Rahayu Ningsih (BIMA : Journal of Business and Innovation Management, 2020)
The purpose of this study was to determine the effect of store atmosphere and service quality on consumer satisfaction at Asela Sampang restaurant. This type of research used in this study is quantitative by using multiple linear regression. Data collection in this research is by distributing questionnaires to 100 respondents who visited Asela Sampang restaurant with Asela restaurant consumers who have made purchases at least 2 times, and the sampling technique is non probability sampling with purposive sampling method. The testing technique in this study is the validity and reliability test, while the data analysis technique uses the classic assumption test (normality test, heteroscedasticity, multicollinearity, autocorrelation, linearity), while the hypothesis test is t test, F test and coefficient of determination. The results showed that store atmosphere and service quality affect customer satisfaction.